Jonás y la ballena rosada - Valdivia, Juan Carlos; García, Dino; Prudencio, María Renée, 1974-; Lobo, Claudia; Montes, José Wolfango, 1951- (Periodistas Asociados Televisión, 1995)
This film chronicles the misadventures of Julia and her brother-in-law, Jonah, a teacher at a private girls' school. His troubles began when he married the wealthy daughter of an eccentric family. His snooty father-in-law has never concealed his disapproval of Jonah's modest social standing. His wife is unable to enjoy sex and this adds further tension. Eventually the frustrated Jonah allows Julia to seduce him. Unfortunately, the family finds out and to save face, sends Julia to the United States. The family soon falls into financial ruin. Meanwhile, Julia falls in love with a powerful drug lord and because of this, tragedy ensues.